Taxonomic revision of Pseudorhopalia Wilcox & Papavero, 1971 (Insecta, Diptera, Mydidae, Rhopaliinae), with description of a new species from the Brazilian Amazon - Calhau, Julia; Nihei, Silvio Shigueo; Lamas, Carlos José Einicker (Zootaxa, 2014)
The previously monotypic genus Pseudorhopalia Wilcox & Papavero, 1971 is here revised, with description of a new species, Pseudorhopalia manauara, sp. n. The type-species, P. mirandai (d’Andretta & Carrera, 1951), is only found in northeastern Brazil, in the semiarid Caatinga biome. On the other hand, the new species is found in the humid Brazilian Amazonia, within dense ombrophilous forest and campina (scleromorphic scrub vegetation associated with white sand).